Chemical Constituents of Glycosmis Calcicola and G. Rupestris (Rutaceae) and Their Biological Activities - Chew, Yean Ling (1995)
Investigation of the leaf and tvig sex tracts of Glycosm is calcicola (Rutaceae) from two different locations has led to the isolation of five compounds. The structures of the secompounds were elucidated by means of spectroscopic methods(IR, uv, ¹H-NMR, ¹³C- NMR, MS)and by comparison with previous studies. G. calcicola collected from Langk aviIsl and yielded ethyl gerambullin Isitosterol and another unidentified compound .From another separate collection of the same plant from Templer Park, a new alkaloid (desmethoxyzanthophylline)and f1indersine have also been isolated. A similar study on the bark of another species, G. rupestris, collected from Langkawi Island afforded methoxyglycomaurin), a new alkaloid (7-glycomaurin, des-Nmethylacronycine and stigmast-7-enol, while the leaves of the plant gave an unidentified compound. The antifungal activities of these plant extracts were evaluated using the poison food and spore germination techniques. The plant extracts exhibited varying degree of fungitoxic response on the growth of the fungal pathogens of chilli (Capsicum annuum L.). The chloroform extract of G. calcicola collected from Templer Park has been shown to be most effective in inhibiting the mycelial growth, sporulation and spore germination of Chaonephora cucurbi tarium, Col1etotrichum capsici and C. gloeosporioides. The antifungal compounds in this extract were identified using TLC bioassay technique against Aspergillus flavus. The results indicated that the activity of the extract is due to the presence of its major components: flindersine and desmethoxyzanthophylline.